Relationship between Dimorphology and Respiration in Mucor genevensis Studied with Chloramphenicol - Clark-Walker, G. D. (1973)
Growth of Mucor genevensis, a facultatively anaerobic dimorphic mold, in high concentrations of chloramphenicol (4 mg/ml) leads to increased numbers of yeast-like cells and small club-like mycelial forms. This change in morphology is accompanied by a threefold increase in the mass doubling time, the loss of cyanide-sensitive respiration, and the development of cyanide-insensitive respiration. Associated with these changes is the absence of cytochromes aa(3) and b and the inability of the organism to utilize ethanol; in addition, mitochondria appear more numerous and have less internal membrane. A further inhibitory action of the antibiotic, other than eliminating functional mitochondria, appears likely since microaerobic cultures which lack respiratory ability have twice the mass doubling time in the presence of the drug. Although a small inhibition of amino acid incorporation by cytoplasmic ribosomes is found with a high chloramphenicol concentration, it is insufficient to account for the effect on growth of the microaerobic culture. The nature of this additional effect of chloramphenicol remains to be determined, but it has been shown that increasing the glucose concentration can partially reverse this action of the antibiotic. The effect of the drug on the morphology of the organism is not as dramatic as that of phenethyl alcohol in producing yeast-like forms. However, in view of the action of chloramphenicol in eliminating functional mitochondria in M. genevensis the suggestion that phenethyl alcohol exerts its effect in promoting yeast-like morphology by uncoupling oxidative phosphorylation should be re-examined.